PECULIARITIES OF DIGITAL TRANSFORMATION IN THE CONTEXT OF MARKETING MANAGEMENT OF A SOLAR POWER PLANT CONSTRUCTION ENTERPRISE - DIDENKO, Yevhen (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article highlights the theoretical and applied aspects of digital transformation in the context of marketing management at enterprises operating in the field of solar power plant construction. The relevance of the study is due by increasing demands for energy efficiency, environmental sustainability, and the urgent need for businesses to adapt to the conditions of the digital economy. The author emphasizes that digital transformation encompasses the modernization of technological infrastructure as well as the restructuring of management logic, corporate culture, and customer interaction models. The paper analyzes modern approaches to the application of digital tools in marketing activities, with special attention paid to CRM systems, analytical platforms, automated marketing services, chatbots, personalized communication channels, and artificial intelligence tools. There has been substantiated the functional role of these solutions in the processes of decision-making, planning of advertising campaigns, customer experience management and formation of customer loyalty. A gradual model of digital technologies implementation has been proposed, which includes audit of marketing processes, selection of relevant tools, automation of routine operations, staff training and analysis of the effectiveness of transformational changes. It has been found that modern marketing management in the solar power plant construction sector is based on the use of a comprehensive set of digital tools covering communication automation, analytics, artificial intelligence, and interactive technologies. Their integration into business operations ensures strategic flexibility, enhanced customer focus, and greater project efficiency. The results of the analysis conclude that digitalization of marketing management is a strategic direction for the development of enterprises in the renewable energy sector. Future research prospects are related to the deepening of digital maturity assessments of energy companies, development of industry-specific models for marketing automation, and investigation of the impact of artificial intelligence on management decision-making.
Keywords: digital transformation; digital marketing; marketing management; solar power plant construction enterprise; technology implementation; marketing strategies; marketing campaigns